PENGARUH KEPUASAN KERJA, KOMITMEN ORGANISASIONAL, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN (Studi pada PT. Nayati Indonesia, Semarang) - Yansen P, Alphonso; Rahardja, Edy (Faculty of Economics and Business Diponegoro University, 2017)
This study is purposed to analyze the effects of job satisfaction, organizational commitment, and organizational culture on employee’s performance. The phenomenon of fluctuation employee’s performance rate at PT. Nayati Indonesia, Semarang indicate that the employee’s performance is not maximized. This study used three independent variables there are job satisfaction, organizational commitment, and organizational culture. This study aims to examine and analyze the effects of job satisfaction, organizational commitment, and organizational culture on employee’s performance at PT. Nayati Indonesia, Semarang. Data collection methods used in this study are questionnaires using random sampling method, the sample used in this study were permanent employees of PT. Nayati Indonesia, Semarang who have worked for at least two years as many as 84 respondents. This study uses data analysis methods include validity test, reliability test, classic assumption test, multiple linear regression analysis, coefficient determination test, F test and t test. The result showed that the variables of job satisfaction, organizational commitment and organizational culture affect positively on the employee’s performance of employees at PT. Nayati Indonesia, Semarang. These variables have an impact of 57,9% on employee’s performance. While the remaining 42.1% is influenced by other variables outside of this study